A Staphylococcus aureus clpX Mutant Used as a Unique Screening Tool to Identify Cell Wall Synthesis Inhibitors that Reverse β-Lactam Resistance in MRSA - Bæk, Kristoffer T.; Jensen, Camilla; Farha, Maya A.; Nielsen, Tobias K.; Paknejadi, Ervin; Mebus, Viktor H.; Vestergaard, Martin; Brown, Eric D.; Frees, Dorte (Frontiers in Molecular Biosciences, 2021)
Staphylococcus aureus is a leading cause of bacterial infections world-wide. Staphylococcal infections are preferentially treated with β-lactam antibiotics, however, methicillin-resistant S. aureus (MRSA) strains have acquired resistance to this superior class of antibiotics. We have developed a growth-based, high-throughput screening approach that directly identifies cell wall synthesis inhibitors capable of reversing β-lactam resistance in MRSA. The screen is based on the finding that S. aureus mutants lacking the ClpX chaperone protein grow very poorly at 30ºC unless specific steps in teichoic acid synthesis or penicillin binding protein (PBP) activity are inhibited. This property allowed us to exploit the S. aureus clpX mutant as a unique screening tool to rapidly identify biologically active compounds that target cell wall synthesis. We tested a library of ~50,000 small chemical compounds and searched for compounds that inhibited growth of the wild type while stimulating growth of the clpX mutant. Fifty-eight compounds met these screening criteria, and preliminary tests of 10 compounds identified seven compounds that reverse β-lactam resistance of MRSA as expected for inhibitors of teichoic acid synthesis. The hit compounds are therefore promising candidates for further development as novel combination agents to restore β-lactam efficacy against MRSA.